2004
DOI: 10.1523/jneurosci.4483-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Galectin-1 Stimulates Macrophages to Promote Axonal Regeneration in Peripheral Nerves after Axotomy

Abstract: Various neurotrophic factors that promote axonal regeneration have been investigated in vivo, but the signals that prompt neurons to send out processes in peripheral nerves after axotomy are not well understood. Previously, we have shown oxidized galectin-1 (GAL-1/Ox) promotes initial axonal growth after axotomy in peripheral nerves. However, the mechanism by which GAL-1/Ox promotes axonal regeneration remains unclear and is the subject of the present study. To identify possible target cells of GAL-1/Ox, a flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 48 publications
3
72
1
2
Order By: Relevance
“…20,33 It has been shown that oxidized galectin-1 acts directly on macrophages, which in turn may produce a factor that promotes axonal growth. 33 We have shown earlier that exposure to kainate significantly increases oxidative stress in the hippocampus and that oxidative damage of cellular components is accumulated in hippocampal neurons, astrocytes, and microglias. 21 Therefore, we suggest that astrocytesecreted galectin-1, which is likely to be mostly oxidized, may function in promoting neurogenesis in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…20,33 It has been shown that oxidized galectin-1 acts directly on macrophages, which in turn may produce a factor that promotes axonal growth. 33 We have shown earlier that exposure to kainate significantly increases oxidative stress in the hippocampus and that oxidative damage of cellular components is accumulated in hippocampal neurons, astrocytes, and microglias. 21 Therefore, we suggest that astrocytesecreted galectin-1, which is likely to be mostly oxidized, may function in promoting neurogenesis in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated macrophages after PNS injury, for example, produce Schwann cell migration factor (Horie et al, 2004) survival, e.g., brain-derived neurotrophic factor (BDNF), interleukin (IL)-6, or glial cell line-derived neurotrophic factor (Batchelor et al, 1999;Dougherty et al, 2000;Leskovar et al, 2000). In fact, BDNF is especially shown to be involved in collateral branching from regenerating motor axons (Streppel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…41 In vitro studies using DRG explants revealed that oxidized Gal-1a directly stimulates macrophages to secrete a factor that promotes axonal growth; 42 however, many important questions remain to be answered. Concerning Gal-1b, we must clarify whether or not Gal-1b also acts on macrophages, and whether the oxidation of cysteine residues in Gal-1b is required for such regeneration.…”
Section: Discussionmentioning
confidence: 99%